Return to Original Homes and Its Relationship to Family Stability among Displaced Families after the Derna Storm - Elzunni, Hamza Yousef ((Faculty of Arts Journal) مجلة كلية الآداب - جامعة مصراتة, 2026)
This study aims to analyze the relationship between returning to the original residence and the restoration of family stability, as well as the transformations in social relations among families affected by Storm Daniel in the city of Derna following displacement. The study adopted a qualitative approach, with data collected through semi-structured interviews conducted with a sample of twelve (12) heads of households who had returned to their homes. The participants were selected using the snowball sampling technique. The data were then analyzed using thematic analysis. The findings revealed that returning to the original residence contributed to enhancing family stability and rebuilding social ties, despite the persistence of certain challenges related to housing conditions. The results also indicated that social and institutional support played an important role in assisting families and promoting social recovery after the disaster.